Caccioppoli-type estimates for a class of nonlinear differential operators - Tiryaki, A. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We establish Caccioppoli-type estimates for a class of nonlinear differential equations with the aid of a differential identity that generalizes the well-known multidimensional Picone’s formula. In special cases, these estimates give the Finsler p-Laplacian, the p-Laplacian and the pseudo-p-Laplacian.